UPF1/SMG7-dependent microRNA-mediated gene regulation - Jungyun Park (Nature Portfolio, 2019)
UPF1 mediates the decay of target mRNA in a 3′ untranslated region (UTR)-length-dependent manner. Here the authors reveal that the 3′UTR-length-dependent regulation of UPF1-dependent mRNA decay occurs through EJC-independent but miRNA-dependent regulation.